THE RELATIONSHIP BETWEEN WOMEN'S ATTITUDES TOWARD EARLY DIAGNOSIS OF CERVICAL CANCER AND HEALTH LITERACY LEVELS - Birnur YEŞİLDAĞ (Rojan GÜMÜŞ, 2023)
The purpose of this study is to determine the relationship between women's attitudes toward early diagnosis of cervical cancer and their health literacy levels. The sample of the descriptive and cross-sectional study consisted of 714 women aged 30 to 65 who lived in a district center. Data were collected through the "Personal Information Form", the "Attitude Scale Towards Early Diagnosis of Cervical Cancer (ASTEC)" and the "Health Literacy Scale (HLS)". Data were analyzed using SPSS (Statistical Package for Social Sciences) for the Windows 16.0 program. Percentage distribution, t-test, ANOVA test, and Spearman correlation were used for data analysis, and statistical significance was accepted p<0.05. The participants' ASTEC total mean score was found 95.33±7.64, and their HLS mean score was found 82.32±20.33. A statistically significant and positive correlation was detected between both scales. A significant relationship was found between the scale mean scores and education, economic condition, knowledge of cervical cancer, and knowing and having the pap-smear test. Increasing women's health literacy levels and raising their awareness are important for the elimination of cervical cancer.